Allah yang Memiliki Kesetaraan Sosial: Tafsir Amos 4:1-3 - Firman Panjaitan; Ruth Anugrah Olivia (Predica Verbum: Jurnal Teologi dan Misi, 2023)
It is undeniable that today's social reality often portrays injustice. Many events show how the privileges of the strong have weakened and oppressed the weak. This situation also occurred during the time of Amos as a prophet. The strong oppress the weak and make the social situation unbalanced. The purpose of this study is to find God who is on the side of the weak and seek social justice for community life. The method used in this study is qualitative with critical interpretation approach. The results reveal that God, as preached by Amos, is a god of social equality and favor, especially to those who are weakened and marginalized. Because God is on the side of the weak, God's people must also show their partiality to the weak and poor.